Răspunsuri

2014-11-01T23:49:11+02:00
M= mijlocul [AB]                  
                              ⇒    [AM]=[MB] = 3√3 cm.
[AB]= 6√3 cm    

In ΔNAM 
m ( A) = 90°   ⇒ Teorema lui Pitagora : ip² = c1² + c2² 
                                                         NM²= NA² + AM²
                                                         6² = NA² + 3√3
                                                         36= NA² + 27
                                                         NA² = 36-27
                                                         NA²= 9
                                                         NA = √9 ⇒ NA = 3 cm. 
N= mijlocul [AA'] ⇒ [A'N]= [NA]
                              NA= 3 CM   ⇒ [A'N]= 3 cm. 
 
 AA' = NA + A'N
 AA' = 3 + 3 CM
 AA' = 6 CM. 
                                 


12 5 12